Informed trading in peers of M&A firms: Evidence from M&A advisor banks - LI, Xuanbo (Institutional Knowledge at Singapore Management University, 2024)
M&A advisor banks are privy to valuable and sensitive information through their service. I examine whether M&A advisor banks exploit such private information to trade in peers of M&A firms. I provide evidence that M&A advisor banks gain higher profits through their trading in peers of M&A firms, compared with non-advisor banks. Such informed trading is more intensive for M&A deals with larger impacts on peer firms (i.e., when the deal value is more significant for peer firms; when the M&A firms have larger market share in the industry; and when the stock price reactions of peer firms are stronger). Further analysis reveals that prior business relationships with peer firms enable M&A advisor banks to engage in such informed trading. In addition, M&A advisor banks’ performance pressure incentivizes them to utilize private M&A information for trading, while reputation concern deters such informed trading in peer firms.